Association of maternal dietary patterns with child birth weight and size in India: Evidence from National Family Health Survey, 2005 to 2016 - Brajesh, Brajesh; Shekhar, Chander (Indian Journal of Child Health, 2021)
Background: Maternal dietary diversity during pregnancy is a major determinant of birth weight and birth size of infant. During pregnancy, mother diet is highly dependent on their topographical, cultural, and sociodemographic circumstances. Objective: The objective of the study was to assess the association between the maternal dietary intake with child birth weight and birth size along with the sociodemographic factors in India. Materials and Methods: The data for this study were drawn from the National Family Health Survey (NFHS), 2005 to 2006 and 2015 to 2016 held in India. Inferential statistical analysis Chi-square was built to test was used to examine the association between maternal dietary patterns, and logistic regression model was used to analyze the effect of mother’s dietary patterns on child birth weight and size by controlling the sociodemographic factors. Results: Mother’s daily intake of fish, meat, green leafy vegetables, and fruits was associated with higher birth weight or size and lower risk of intrauterine growth retardation. Women with ?2 dietary diversity categories had significantly higher proportion of low birth weight (LBW) and size of babies comparatively to those in the ?2 dietary diversity categories, there were lesser chance of LBW and small size of babies with women’s dietary diversity 3 (odds ranges from 1.09 to 1.44) or ?4 (odds ranges from 1.15 to 1.59). Furthermore, low birth order, mother’s underweight status, low maternal education, and wealth status significantly have positive association with the poor birth outcomes. Conclusion: The birth weight and size of newborns were found positively associated with the mother’s dietary intake. To meet the aim of maternal dietary diversity and to achieve the double bonus, the government should focus more on supplementation and food security programs during pregnancy that also include nutritional education as well as behavioral and social change interventions strategies.